(untitled) (PJDOL, 2023)
The purpose of the study was to find out student’s experiences towards learning through social learning sites (SLSs) such as YouTube, blogs, Wiki-spaces classroom, Edmodo, Skype, Academia.edu, Research Gate etc. in sharing and learning new things or ideas in higher education and the challenges they faced. The participants of the study were students of BS Hons (Final semester) and MS from Lahore College for Women University, Lahore. 23 semi structured in-depth interviews and 2 focus group discussions with students were conducted